Do orthodontists aim to decrease the duration of fixed appliance treatment? - Mushriq F Abid; Akram F Alhuwaizi; Ali M Al-Attar (Wolters Kluwer Medknow Publications, 2021)
OBJECTIVES: The aim of the present study was to investigate the trends in the use of fixed appliance and accelerated orthodontics to decrease the treatment duration. Further, this study aimed to assess the effect of demographic factors on the participant's choice of treatment modality. METHODS: This was a cross-sectional study in the form of questionnaire-based online survey especially designed and distributed to 265 orthodontists via email. The questions aimed to collect basic information about the participants and respondents' choices for decreasing the treatment duration. The data were analyzed according to gender, level of academic education and years of clinical experience using Chi-square test. RESULTS: A response rate of 85.2% was reported. Most of the orthodontists aimed to reduce the treatment duration by the biomechanical (66.8%) and surgical approaches (27.4%). The use of sliding mechanics (69.4%) and one-step retraction was more common (66.3%). MBT bracket prescription was more prevalent (51.7%), followed by Roth (41.1%). Conventional brackets were used more than self-ligating brackets, and aesthetic brackets were avoided by one third of the respondents. NiTi wires were the most commonly used wires during the alignment stage (44.2%). However, the effect of gender, years of clinical experience and specialty level of education showed some effects on the use of certain techniques and clinical practice of the respondents. CONCLUSIONS: Most of the orthodontists aimed to decrease orthodontic treatment duration by using biomechanical and surgical approaches. Gender and clinical experience to a certain extent affected the participants' choice during orthodontic treatment.